Does logging affect soil biodiversity and its functions? A review - María Laura Moreno; José Camilo Bedano; Luis Rivera; Natalia Politi (Soil Organisms, 2023)
Silvicultural practices affect over 30 % of the global forest area and are a major driver of forest degradation. Logging is a forest management practice that is becoming increasingly widespread, since it is an important source of income for developing countries. Despite the expanding body of research on aboveground communities, little is known about the effects of logging on belowground communities. We conducted a qualitative systematic literature review to assess the current state of knowledge about the impact of logging on soil biodiversity and ecosystem functions. We addressed the effects of logging operations (e.g., clear-cutting, selective logging) on i) soil organisms (from microorganisms to soil fauna) and ii) soil functions mediated by soil biota. In general, the reviewed articles reported a negative effect of logging operations on abundance and diversity of microorganisms. Regarding soil fauna, most studies focus on insect taxa, with the impact on other soil fauna taxa remaining poorly understood. Decomposition was the most commonly studied ecosystem function. In general, the literature has reported negative effects of logging on soil functions; however, some studies found neutral or positive responses. This review highlights that logging operations have detrimental effects on a variety of different groups of organisms (e.g., microorganisms and insects) and functions (e.g., decomposition, microbial activity, bioturbation). However, on the basis of the evidence to date, low-intensity logging operations can be a beneficial practice for the conservation of soil organisms and ecosystem functions.